Early Postpartum Complications and Maternal Mortality: An Experience of Mymensingh Medical College Hospital, Bangladesh - Alamgir, Sadia Nusrat; Nigar, Kawsar; Nahar, Kamrun (Community Based Medical Journal, 2022)
A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Mymensingh Medical College Hospital (MMCH), Bangladesh, between April and September of 2010, to observe and evaluate common complications in early puerperium. A total of 384 patients were selected for the study, who were admitted with immediate postpartum complications, or who experienced complications after delivery at MMCH. Most of the patients 202(52.6%) belongs to 21-30 years age group followed by 118(30.73%) in >30 years and 64(16.67%) in ≤20 years group. Low parity accounts for most patients, 217(56.5%), while grand multiparity was documented in 42(10.9%) patients. 211(54.95%) patients had no history of antenatal checkup. 179(46.62%) patients had home delivery, while the rest had institutional delivery. 239(62.24%) patients had normal vaginal delivery, while 129(33.6%) had Caesarean operation, 7(1.82%) needed vacuum extraction and 2.34% had forceps’ delivery. 146(38.02%) had their delivery without attending doctor, nurse/midwife or skilled birth attendant. Most of the patients, 281(73.18%), had their symptoms and signs within 24 hours of delivery, while 41(10.67%) and 62(16.15%) had within 48 hours and within 7 days respectively. Primary postpartum haemorrhage (PPH) was the leading complication found in 114(29.68%) patients, while the other major complications were puerperal sepsis 53(13.8%), urinary tract infection 40(10.42%), postpartum eclampsia 38(9.9%). 329(85.68%) patients were discharged without any morbidity; however, maternal mortality was observed in 18(4.68%) cases. Puerperal sepsis 5(28%), postpartum eclampsia 4(22%) and pulmonary embolism 3(17%) were the leading causes of mortality. Skilled obstetric care, active management of third stage of labour, prevention and treatment of anaemia, and maintenance of strict asepsis during delivery can prevent a considerable incidence of those complications. CBMJ 2021 January: vol. 10 no. 02 P: 85-90